Anticancer activity of Pupalia lappacea on chronic myeloid leukemia K562 cells - Ravi, Alvala (BioMed Central, 2012)
BACKGROUND: Cancer is one of the most prominent human diseases which has enthused scientific and commercial interest in the discovery of newer anticancer agents from natural sources. Here we demonstrated the anticancer activity of ethanolic extract of aerial parts of Pupalia lappacea (L) Juss (Amaranthaceae) (EAPL) on Chronic Myeloid Leukemia K562 cells. METHODS: Antiproliferative activity of EAPL was determined by MTT assay using carvacrol as a positive control. Induction of apoptosis was studied by annexin V, mitochondrial membrane potential, caspase activation and cell cycle analysis using flow cytometer and modulation in protein levels of p53, PCNA, Bax and Bcl2 ratio, cytochrome c and cleavage of PARP were studied by Western blot analysis. The standardization of the extract was performed through reverse phase-HPLC using Rutin as biomarker. RESULTS: The results showed dose dependent decrease in growth of K562 cells with an IC(50) of 40 ± 0.01 μg/ml by EAPL. Induction of apoptosis by EAPL was dose dependent with the activation of p53, inhibition of PCNA, decrease in Bcl2/Bax ratio, decrease in the mitochondrial membrane potential resulting in release of cytochrome c, activation of multicaspase and cleavage of PARP. Further HPLC standardization of EAPL showed presence 0.024% of Rutin. CONCLUSION: Present study significantly demonstrates anticancer activity of EAPL on Chronic Myeloid Leukemia (K562) cells which can lead to potential therapeutic agent in treating cancer. Rutin, a known anti cancer compound is being reported and quantified for the first time from EAPL.